2011
DOI: 10.1161/circulationaha.110.991125
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Derived Neuregulin Protects the Heart Against Ischemic Injury

Abstract: Background Removal of cardiac endothelial cells (EC) has been shown to produce significant detrimental effects on the function of adjacent cardiac myocytes, suggesting that EC play a critical role in autocrine/paracrine regulation of the heart. Despite this important observation, the mediators of the protective function of EC remain obscure. Neuregulin (NRG, a member of the epidermal growth factor family) is produced by EC and cardiac myocytes contain receptors (erbB) for this ligand. We hypothesized that NRG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(137 citation statements)
references
References 33 publications
6
130
0
1
Order By: Relevance
“…In the heart, NRG-1 is synthesized and released by the endocardial and cardiac microvascular endothelium (1,2). Hedhli et al have reported that NRG-1 plays an important role in cardiac myocyte protection and angiogenic responses to ischemia injury, and NRG-1 secretion is significantly increased in cardiac endothelial cells in response to hypoxia (14). Our study also showed the expression and secretion of NRG-1 were increased in HCMECs with Hypo/SD stimulation.…”
Section: Discussionsupporting
confidence: 78%
“…In the heart, NRG-1 is synthesized and released by the endocardial and cardiac microvascular endothelium (1,2). Hedhli et al have reported that NRG-1 plays an important role in cardiac myocyte protection and angiogenic responses to ischemia injury, and NRG-1 secretion is significantly increased in cardiac endothelial cells in response to hypoxia (14). Our study also showed the expression and secretion of NRG-1 were increased in HCMECs with Hypo/SD stimulation.…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with this idea, it is known that FGF1 regulates cardiac remodeling by exerting a protective and proliferative effect after MI [18,19]. On the other hand, neuregulins play crucial roles in the adult cardiovascular system by inducing structural organization of sarcomeres, cell integrity, cell-cell adhesion [20], cell survival [21,22] and angiogenesis [23]. In fact, several studies using animal models of heart failure have demonstrated the therapeutic benefits of neuregulins, which improved cardiac performance, attenuated disease markers, and prolonged animal survival [24,25].…”
Section: Introductionmentioning
confidence: 78%
“…Studies have demonstrated that in addition to doxorubicin-induced heart failure, Neuregulin1 also improves cardiac function in ischemiareperfusion, viral infection, and pacing induced heart failure (Liu et al, 2006;Bersell et al, 2009;Hedhli et al, 2011). In addition, Neuregulin1 promotes cell cycle reentry of differentiated adult cardiomyocytes, improves angiogenesis in the heart (Bersell et al, 2009;Hedhli et al, 2011), and promotes embryonic stem cell differentiation into the cardiac lineage (Sun et al, 2011). Clinical trials are ongoing using Neureuglin1 for the treatment of heart failure in patients (Gao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hedhli and colleagues tested whether endothelial-derived Neuregulin1s are important for protecting the heart from ischemia-reperfusion injury (Hedhli et al, 2011). They generated mice with tamoxifen-inducible and endothelium-selective Neuregulin1 gene knockout by cross-breeding mice with VE-cadherin promoter driven Cre-ER (Monvoisin et al, 2006) and mice carrying homozygously floxed alleles of the Neuregulin1 gene (Yang et al, 2001).…”
Section: Transgenic Mouse Models With Mutations Of the Neuregulin1 Genementioning
confidence: 99%
See 1 more Smart Citation